NARRATIVE REVIEW: PEMANFAATAN KALSIUM KARBONAT DARI LIMBAH CANGKANG TELUR DALAM PRODUK RUMAH TANGGA RAMAH LINGKUNGAN - Ramlawati Ramlawati; Nadila Pasomba; Mutmainnah; Nurul Maulidia; Sahrani U (JOURNAL SAINS STUDENT RESEARCH, 2026)
Eggshell waste is a type of household organic waste that has not been optimally utilized and has the potential to cause environmental pollution. In fact, eggshells contain very high calcium carbonate (CaCO₃), reaching 90–97%, enabling them to be processed into various environmentally friendly and economically valuable household products. This study aims to comprehensively review the utilization of calcium carbonate from eggshell waste in environmentally friendly household products. The method used was a narrative review with literature searches through the Google Scholar database covering the 2019–2025 period, yielding 20 relevant articles that were systematically analyzed. The results show that eggshells are effectively utilized in agriculture as organic fertilizer to neutralize soil pH, in environmental applications as adsorbents for heavy metals, and in household products such as antibacterial toothpaste, aromatherapy candles, natural abrasive materials, and various aesthetically valuable crafts. The success of this utilization is greatly influenced by processing methods, particle size, calcination temperature, and material purity. In conclusion, eggshell waste has great potential as an alternative raw material supporting the concepts of zero waste, circular economy, and sustainable development. Further research is needed on long-term product stability, industrial-scale cost-benefit analysis, and safety tests for direct human applications.